Strength and durability of concrete containing recycled concrete aggregates. (September 2018) - Thomas, Job; Thaickavil, Nassif Nazeer; Wilson, P.M.
Abstract: Recycled concrete aggregates (RCA) sourced from waste concrete are a sustainable alternative to natural crushed stone aggregates. The strength and durability properties of concrete containing RCA were evaluated by a comprehensive experimental investigation involving nine control mixes. The variables considered in the experimental study are water cement ratio, cement content in concrete and percentage replacement of coarse aggregate. The strength properties such as compressive strength, modulus of elasticity, splitting tensile strength and flexural strength are studied. Durability properties such as water absorption, sorptivity, acid attack resistance and chloride permeability are also determined. The test results showed that up to 25% of natural crushed stone aggregates in concrete may be replaced with RCA, without significantly affecting the strength of concrete and that the partial replacement of natural aggregates with RCA can be recommended in areas of moderate exposure conditions. Mathematical models developed in the study can be used for the a priori prediction of the strength parameters of RCA concrete. A mix design methodology using the developed models is proposed to aid practicing engineers to determine the mix proportions of RCA concrete.